ACCOUNTING AND ANALYTICAL SUPPORT OF FOREIGN ECONOMIC ACTIVITY OF UKRAINIAN ENTERPRISES IN TERMS OF ITS TYPES - Prokopyshyn , О.; Leha , О.; Tiutiunnyk , С.; Humeniuk , І. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article advocates for enhanced accounting and analytical support for the foreign economic activities (FEA) of Ukrainian enterprises in light of globalization, currency fluctuations, and evolving tax and customs regulations. It emphasizes that effective management of foreign exchange necessitates not only suitable regulatory frameworks but also a tailored accounting and analytics system that accommodates the specificities of various FEA types. The essential characteristics of the primary types of foreign trade are outlined in accordance with the Law of Ukraine “On Foreign Economic Activity”, followed by an analysis of how these are represented in accounting. The article summarizes challenges related to the recording of export-import operations, transactions involving raw materials, licensing fees, investments, and other forms of foreign exchange, particularly focusing on currency, tax, customs, and documentation aspects. It is identified that many of these challenges stem from the fragmentation of accounting policies, insufficient process automation, and limited access to analytical information on foreign markets. To address these issues, the article suggests the adoption of modern digital solutions, such as ERP systems, electronic document management (EDI), and Business Intelligence tools, which would facilitate the integration of accounting and analytics into a cohesive information space. The transition to international financial reporting standards (IFRS) and the engagement of international tax planning specialists are believed to enhance the transparency of foreign exchange operations and improve management efficiency. Future research prospects in this field are focused on developing integrated models for accounting and analytical support related to foreign exchange, which are tailored to accommodate digital transformation and international reporting requirements. Particular emphasis should be placed on creating a unified accounting framework for complex cross-border transactions that involve multi-level supply chains. Additionally, there is a need to investigate the impact of sanctions, changes in customs regulations, and transfer pricing on accounting practices.